2023
DOI: 10.3390/sports11100194
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits vs. Sports Classes of Polish Representatives in Junior Sports Acrobatics

Paweł Piepiora,
Adrianna Naczyńska

Abstract: The aim of this paper was to determine the influence of adolescence, training discipline, and training regime on the personality formation of adolescent sports acrobats. Therefore, the purpose of this paper was to study the relationship between the personality traits and the sports classes of Polish junior sports acrobatics representatives. The respondents (N = 90) were juniors aged 18–19 and were divided into three samples: (1) n = 30 Polish representatives in sports acrobatics with a first or master sports c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is important to consider individual differences when designing interventions to enhance performance. Piepiora and Naczy ńska [25] investigated the relationship between personality traits and sports classes in junior sports acrobatics. Their findings suggest that athletes with different personality profiles might respond differently to training approaches.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider individual differences when designing interventions to enhance performance. Piepiora and Naczy ńska [25] investigated the relationship between personality traits and sports classes in junior sports acrobatics. Their findings suggest that athletes with different personality profiles might respond differently to training approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, personality traits, such as neuroticism, were positively and significantly related to high anxiety during the COVID-19 pandemic [12,43]. Some authors have also demonstrated that low levels of neuroticism can help individuals to maintain a sense of security in stressful situations and develop curiosity about the external and internal world [44].…”
Section: The Multidimensional Structurementioning
confidence: 99%